Herkes için Astronomi ve Astronomi Fotoğrafçılığı - Batman, Alp; Şirin, Ferhat; Şirin, Nermin (İstanbul Kültür Üniversitesi Yayınları, 2005)
Amatör astronomi, mühendislik ve temel bilimler ve sosyal bilimler gibi çok farklı alanlarla ile doğrudan ilişkili olduğundan her yaştan, her meslekten insanların hayat boyu zevkle uğraşabilecekleri bir hobidir. Genelde amatör astronomi ile ilgilenmeye başlayan insanlar bilgi açıklarını çok hızlı bir şekilde kapatma ihtiyacı duyarlar. Bu noktada, doğru bir başlangıç yapmak, hayal kırıklığına uğramaları en aza indirmek açısından çok önemlidir. Bu bildiride, kurulu amaçlanan biri amatör astronomiyi halka sevdirmek ve yaymak olan Ali Kuşçu Amatör Astronomi Topluluğunun yaptığı aktivitelerden edindiği deneyimler anlatacaktır. Ayrıca topluluğun, astronominin önemli bir kolu olan astronomi fotoğrafçılığı konusunda yaptığı çalışmalar verilecektir. Bu bildirinin amaçlarından biri de, ister gözlem isterse astronomi fotoğrafçılığı konusunda olsun astronomiden beklentilerin fazla masraflara girilmeden de karşılanabileceğini ve bundan da zevk alınabileceğini göstermektir.

Amateur Astronomy is a nice hobby for everyone. It is related to many branches of science such as engineering, social and fundamental sciences. Generally, first of all the person who is interested in Amateur Astronomy needs many useful information about it. The most important thing is to start in a right way. Ali Kuşçu Amateur Astronomy club was built for this requirement. The aim of our club is to help someone to love astronomy and start astronomy rightly. This paper consists of a guide for beginners and describes how to use a camera in astronomy. It is called astrophotography. This paper tells our experiences about astrophotography and shows you our photos. You can take some ideas from them. One of the aims of this paper is to show people right way to start astronomy and whatever their finance condition are, they can meet their requirements and learn Astronomy and be happy. First of all, look to the sky, see Milky Way, be happy, be curious to learn more information about astronomy.
Keywords: Astronomi; Astronomi Fotoğrafçılığı; Amatör Astronomi; Amatör Astronomi Topluluğu; Astronomy; Astronomy Photography; Amateur Astronomy; Amateur Astronomy Community